Land Law and the Security of Farmers’ Land-use Rights in Viet Nam: Development and Challenges in Transition - Lan Huong, Nguyen (VNU Journal of Science: Legal Studies; Vol 38 No 1, 2022)
Land tenure security is important to agricultural development, especially in developing countries. Viet Nam’s land law has been significantly improved since its economic reform starting in 1986, and made a great contribution to the enhancement of the security of farmers’ land-use rights. However, in a transition to a modern economy as emerging in Viet Nam, there remain challenges to the security of farmers’ land-use rights such as limitation of arable landholding ceiling, unnecessary procedural provisions of renewals, and no clear-cut transition to modern thinking of law-makers for land use management. These challenges require a further reform of the land law in order to encourage more effective land use for agricultural development and bring larger economic benefits to small farmers.